2009
DOI: 10.1177/1403494809350518
|View full text |Cite
|
Sign up to set email alerts
|

Practices and representations of health education among primary school teachers

Abstract: Teachers can take different approaches to HE. Teachers' representation of HE plays an important role in the development of HE activities: some teachers consider that HE is the mission of the health professionals and the parents. Our expectations of teacher involvement should be realistic, should take into account the representations of their role, the difficulties they encounter, and should be sustained by specific training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
2
14
0
3
Order By: Relevance
“…If teachers possessed a higher level qualification in health education, then this increased the probability of their teaching about medicines-related topics. This finding is in accordance with earlier studies on health/sex education, that is, teachers who had received adequate basic education or undertaken continuing education in that topic were more likely to teach that subject (Apostolidou and Fontana, 2003;Jourdan et al, 2010;Ramiro and De Matos, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…If teachers possessed a higher level qualification in health education, then this increased the probability of their teaching about medicines-related topics. This finding is in accordance with earlier studies on health/sex education, that is, teachers who had received adequate basic education or undertaken continuing education in that topic were more likely to teach that subject (Apostolidou and Fontana, 2003;Jourdan et al, 2010;Ramiro and De Matos, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Previous French studies showed that the prevalence of teachers' HP practices is at least 70% [30]. The calculation of the minimum sample size with an acceptable error of 5% and a margin of error of 5% using the Cochran's formula [31] gives the results of 314 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…He is a part of education in general because it has the same characteristics and requires learners' active participation [21]. For many years, public health data sources have advocated for the development of prevention and HE [3,[22][23][24][25]. Many research studies have highlighted the role of schools in improving the health of populations [26] and in guiding students towards freedom and responsibility regarding health concerns.…”
Section: Introductionmentioning
confidence: 99%